Variaciones morfométricas de Pseudothelphusa belliana (Decapoda: Pseudothelphusidae) en Michoacán, México - García-Madrigal, Maria del Socorro (1998)
A total of 37 specimens of the freshwater crab Pseudothelphusa belliana were collected from four new localities in the state of Michoacan. Morphometric variation, specially carapace width ( x = 48.7, S.D. x = 3.3 for Chucutitán versus x = 33.5, S.D. x = 9.1 for the rest of specimens), shape of chela, coloration in vivo, and differences on gonopods of two geographically separate populations, suggest two subspecies or a cryptospecies complexo Diagnosis, habitat and distributional data are a1so included.